Evaluating a system to promote timely detection of cognitive impairment in primary care practice. (31st December 2021) - Fitzpatrick, Annette L; Belza, Basia; Raetz, Jacqueline G.; Suchsland, Monica Zigman; Illes, Judit; Gaster, Barak
Abstract: Background: Dementia and mild cognitive impairment (MCI) are underdiagnosed with evidence indicating that clinical diagnoses frequently occur late in the process of cognitive decline. Increasing evidence that dementia may be preventable or delayed has led to an international focus on earlier evaluation, diagnosis and intervention. Method: Using the impetus of "Memory Brain Wellness" as a priority growth program at University of Washington (UW) Medicine, we are developing synergistic strategies to improve timely detection of cognitive impairment across primary care in 15 neighborhood clinics in the Pacific Northwest. This presentation will describe current quality‐improvement efforts to promote engagement across multiple stakeholders including health‐care system leadership, practice care management, primary care providers (PCPs) and clinic staff. This lifespan approach is based on the KAER (Kickstart‐Assess‐Evaluate and Refer) Model and Toolkit (2020 Edition) developed by the Gerontological Society of America (GSA). Results: Program activities to be described include 1) results of interviews with the primary care team to determine acceptability and support needed to implement timely cognitive evaluation; 2) implementation of a training intervention to initiate discussions, conduct cognitive assessment, and manage care; and 3) identification of support services and resources to be used in provider consultation. Input from a Technical Advisory Committee and local Community Advisory Board were incorporated into the training and resource inventory for patient/caregiver support. Topics in the training include normalizing the conversation, team approach, moving toward evaluation, assessment tools, alternate diagnoses/modifiable risk factors, multi‐disciplinary and community referrals, patient counseling, long‐term management, and advance care planning. Changes in practice patterns of PCPs will be reviewed using extracted data from the electronic health record (EHR). Details of each strategy will be provided to explain system‐wide decisions, pragmatic applications, results of trainings held to‐date and feed‐back from the primary care team. Conclusion: This is the first study to refine and utilize the GSA KAER toolkit addressing change in practice patterns in a large multi‐clinic primary care system. Results of this program will be used to extend efforts beyond the Seattle region to address timely cognitive evaluation across the 5‐state WWAMI region (Washington, Wyoming, Alaska. Montana and Idaho) served by UW Medicine.